Anthropometric and motor performance profile of elite futsal athletes - Leandro Ricardo Altimari; Raphael Mendes Ritti Dias; Ferdinando Oliveira Carvalho; Edilson Serpeloni Cyrino; Katiucia Meneguzzi dos Santos; Ademar Avelar; Luis Alberto Gobbo (Universidade Federal de Santa Catarina, 2008)
The purpose of the present study was to identify the anthropometric and motor performance profile of futsal (indoor soccer) athletes in the second and third-placed teams in the Parana state championships (Brazil). Anthropometric (body mass, stature and skinfolds thickness) and motor performance (modified abdominal test, shuttle run, race of 30 m and 40 s) measures were obtained from twenty-seven male athletes (24.7 ± 6.4 years; 73.6 ± 7.6 kg; 174.8 ± 6.6 cm). For data analysis, athletes were grouped according to game positions. ANOVA one-way was used for comparisons between different positions, followed by Scheffé's post hoc test, with p < 0.05. Signifi cant differences were detected in body mass (midfi elder < goalkeeper, p < 0.01), stature (midfielder < forward and goalkeeper, p < 0.01) and lean body mass (midfielder < goalkeeper, p < 0.01). No signifi cant differences in motor performance were detected between the athletes studied. The results of this study show that futsal athletes playing in different positions exhibit similar anthropometric and motor performance, in the majority of variables. ABSTRACT Este estudo objetivou identificar o perfil antropométrico e o desempenho motor de atletas de futsal masculino, pertencentes às equipes finalistas do campeonato paranaense da categoria adulto, chave ouro. Para tanto, coletou-se medidas antropométricas (massa corporal, estatura e espessura de dobras cutâneas) e de desempenho motor (testes abdominal modificado, shuttle run, corrida de 30 m e corrida de 40 s) de vinte e sete atletas (24,7 ± 6,4 anos; 73,6 ± 7,6 kg; 174,8 ± 6,6 cm), do sexo masculino. Para a análise dos dados, agrupou-se os atletas de acordo com a posição de jogo. Anova one-way foi empregada para as comparações entre os jogadores das diferentes posições, seguida pelo teste post hoc de Scheffé, com P < 0,05. Verificou-se diferença signifi cante entre os jogadores de diferentes posições de jogo nas variáveis: massa corporal (alas < goleiros, P < 0,01), estatura (alas < pivôs e goleiros, P < 0,01) e massa corporal magra (alas < goleiros, P < 0,01). Não foram observadas diferenças significantes entre os jogadores das diferentes posições de jogo nas variáveis de desempenho motor. Os resultados encontrados no presente estudo sugerem que atletas de futsal apresentam, na maioria das variáveis analisadas, características antropométricas e de desempenho motor semelhantes entre as posições de jogo.